Pengaruh Globalisasi dan Modernisasi Terhadap Munculnya Risiko Individualisme di Masa Pandemi Covid-19 - Sirah Robitha Maula; Sindi Dewi Aprillian; Sheila Agustina (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
At present, the widespread influence of globalization is no stranger to the ears of modern society. Globalization is a worldwide process that causes the emergence of science and technology advances that affect the pattern of changing lifestyles that are becoming more modern. This also coincides with the emergence of modernization in society which then has an impact on the emergence of individualism in society. individualism is considered as an attitude of prioritizing personal needs without thinking about the needs of society at large. During a pandemic, for example, due to the application of restrictions on interactions between individuals that make individuals spend more time at home and take advantage of available technological sophistication, this is also the reason for the emergence of individualism. Also during the pandemic, the attitude of individualism that appeared in society was the emergence of the term panic buying where individuals buy daily needs on a large scale without having a sense of care for other people who also need those needs. This paper aims to find out how globalization and modernization have affected the emergence of panic buying during a pandemic. Data collection in this paper uses literature studies, where data collection uses books, journals, and other written works. The theory used is the theory of Anthony Giddens about modernity. h the covid 19 pandemic that hit various countries has affected human life in various ways. The pandemic has also led to an attitude of individualism that has diluted the original values that are deeply embedded in the Indonesian nation.